Association of N-acetylcysteine use with contrast-induced nephropathy: an umbrella review of meta-analyses of randomized clinical trials - Zhu, Rong; Zheng, Rong; Deng, Bing; Liu, Ping; Wang, Yiru (Frontiers in Medicine, 2023)
Background The effectiveness of N-acetylcysteine (NAC) in treating contrast-induced nephropathy (CIN) has been the subject of conflicting meta-analyses, but the strength of the evidence for these correlations between NAC use and CIN has not been measured overall. Objective To evaluate the data from randomized clinical studies (RCTs) that examined the relationships between NAC use and CIN in meta-analyses. Methods Between the creation of the database and April 2023, searches were made in PubMed, Cochrane Library, EMBASE, and Web of Science. N-acetylcysteine, contrast-induced nephropathy, or contrast-induced renal disease were among the search keywords used, along with terms including systematic review and meta-analysis. The Assessment of Multiple Systematic Reviews, version 2, which assigned grades of extremely low, low, moderate, or high quality to each meta-analysis’s scientific quality, was used to evaluate each meta-analysis. The confidence of the evidence in meta-analyses of RCTs was evaluated using the Grading of Recommendation, Assessment, Development and Evaluations method, with evidence being rated as very low, low, moderate, or high. Results In total, 493 records were screened; of those, 46 full-text articles were assessed for eligibility, and 12 articles were selected for evidence synthesis as a result of the screening process. Based on the pooled data, which was graded as moderate-quality evidence, it can be concluded that NAC can decrease CIN (OR 0.72, 95% CI 0.65–0.79, p < 0.00001) and blood levels of serum creatinine (MD −0.09, 95% CI −0.17 to −0.01, p = 0.03). In spite of this, there were no associations between NAC and dialysis requirement or mortality in these studies. Conclusion The results of this umbrella review supported that the renal results were enhanced by NAC. The association was supported by moderate-quality evidence. Systematic review registration [https://clinicaltrials.gov/], identifier [CRD42022367811].